PENGEMBANGAN MODEL PENANAMAN PEMBELAJARAN PENDIDIKAN KARAKTER BERBASIS CERITA MELALUI KOMIK BAGI SISWA SEKOLAH DASAR KELAS V - Astiarini, Winda (Pascasarjna Universitas Negeri Jakarta, 2016)
Abstrack : The main purpose of this research develop an instructional of character building model for fifth grade elementary school’s students. This research used Research and Development (R&D) method which main core is Dick and Cerey’s model. Before developing proccess begin, author check out the educational journal to make sure for this development process. First journal is published by UNY and the second journal published by Ganesha Education University. Both of that journals said that the using of comics bery usedfull. It helped to support for better instructional process. And next, in this development proces was doing step by step continuely and it used expert review by content expert, instructional design expert, and media expert to get properness test and it also helped by students as the users in the one to one and small group evaluation. The result of this test is indicate that the product is proper to used. And for the next test is effectiveness test by pre test and post test. From that pre test and post test’s result by t-test indicate that there is a difference result between pre test and post test which indicate this comic is effective to used.Keyword : Character Building, comic, and elementary school’s studentsAbstrak : Penelitian ini bertujuan untuk mengembangan sebuah model pembelajaran pendidikan karakter bagi siswa SD kelas V. Penelitian ini menggunakan metode penelitian Research and Development (R&D) dengan model Dick and Carey. Sebelum proses pengembangan yang lebih jauh,pengembang melakukan studi literatur melalui jurnal yang diterbitkan oleh UNY dan Universitas Pendidikan Ganesha. Hasil kedua jurnal tersebut menyatakan bahwa penggunaan komik mampu mendukung pembelajaran yang lebih baik. Kemudian pada proses pengembangan dilakukan dengan urutan yang hirarki dan juga dilakukan expert review melalui ahli materi, ahli instruksional desain, dan ahli media untuk menilai uji kelayakan dibantu dengan siswa sebagai objek pengguna yakni one to one dan small group evaluation. Hasil uji tersebut menyatakan komik ini layak untuk digunakan. Dan tahapan uji selanjutnya adalah uji efektivitas melalui pretest dan posttest. Hasil pretest dan post test yang ada, dihitung melalui uji-t dengan hasil akhir terdapat perbedaan antara pre test dan post test yang mengindikasikan bahwa komik ini efektif digunakan.Kata kunci: Pendidikan Karakter, komik, siswa SD.